2016
DOI: 10.1136/bmj.i708
|View full text |Cite
|
Sign up to set email alerts
|

Different systolic blood pressure targets for people with history of stroke or transient ischaemic attack: PAST-BP (Prevention After Stroke—Blood Pressure) randomised controlled trial

Abstract: ObjeCtiveTo assess whether using intensive blood pressure targets leads to lower blood pressure in a community population of people with prevalent cerebrovascular disease. DesignOpen label randomised controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 23 publications
3
62
0
4
Order By: Relevance
“…After retrieving the full-text version of the aforementioned 21 studies, 1 study was excluded because it did not report data on achieved BP, as well as 6 more studies that included non-IS/TIA population (Table S1 in the online-only Data Supplement). In the final presentation of the literature search results, there was no conflict or disagreement between the 2 reviewers, and the 14 studies that met the study protocol's inclusion criteria [16][17][18][19][20][21][22][23][24][25][26][27][28][29] were included both in the qualitative and quantitative synthesis ( Figure S1). The characteristics of the included studies, comprising a total of 42 736 patients (63.9% men), are summarized in Table 1.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…After retrieving the full-text version of the aforementioned 21 studies, 1 study was excluded because it did not report data on achieved BP, as well as 6 more studies that included non-IS/TIA population (Table S1 in the online-only Data Supplement). In the final presentation of the literature search results, there was no conflict or disagreement between the 2 reviewers, and the 14 studies that met the study protocol's inclusion criteria [16][17][18][19][20][21][22][23][24][25][26][27][28][29] were included both in the qualitative and quantitative synthesis ( Figure S1). The characteristics of the included studies, comprising a total of 42 736 patients (63.9% men), are summarized in Table 1.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…Included studies consisted of 11 placebo-controlled RCTs, 16 23 In most studies, stroke was defined according to the still used WHO definition 30,31 as a focal neurological deficit of cardiovascular origin persisting for >24 hours. [17][18][19][20][21][22]27 In 5 of the studies, positive neuroimaging was either sufficient by itself 25,26,29 or additional 23,24 to the clinical presentation above for the final definition of stroke. Final, 1 study reported a duration of focal neurological >48 hours for the definition of stroke, 16 whereas another study provided no definition for stroke.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Es gibt weiterhin relativ wenige Studien zur Sekundärprävention nach TIA und Schlaganfall bei Patienten mit erhöhten Blutdruckwerten. Die PAST-BP-Studie untersuchte bei 529 Patienten nach TIA und Schlaganfall eine intensive Blutdrucksenkung mit einem Zielwert von < 130 mmHg versus einem Standardziel von < 140 mmHg [71]. Der mittlere systemische Blutdruck war in der intensiven Behandlungsgruppe nach einem Jahr um 16 mmHg gefallen, in der Standardtherapiegruppe um 13 mmHg.…”
Section: Antihypertensive Therapieunclassified
“… 8 The trial involved active management in all patients, and found that this led to important reductions in BP in both arms. 9 The more intensive target was associated with only a small additional reduction in BP (2.9 mmHg), which raises the question as to whether such an intensive target is cost effective.…”
Section: Introductionmentioning
confidence: 99%